Pterostichus (Platysma) eschscholtzii ... - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Pterostichus (Platysma) eschscholtzii (Germar, 1823) Material. Korsakovo near Khabarovsk, end of June 1997, E. Novomodnyi leg., 1♂; ibid, 08.1997, E. Novomodnyi leg., 1♀; ibid, 06.1999, E. Novomodnyi leg., 2♂, 1♀. Distribution. A subboreal Eastern Palaearctic species: from the Altai Mountains and the Yenisei River in the west to Kamchatka and Japanese islands in the east, from the middle reaches of the Yenisei River, Central Yakutia, and the south of Magadan Region in the north to Southeast Altai, Central Mongolia, Shanghai, and Kyushu Island in the south. ... : Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 581, DOI: 10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734 ...